AN INTEGRATED BULLWHIP EFFECT MEASUREMENT SYSTEM FOR FUZZY MULTI-ECHELON SUPPLY CHAINS - Gumus, Alev Taskin; Guneri, Ali Fuat (YILDIZ TECHNICAL UNIV, 2008)
In this paper, an integrated system is developed that is directed towards the calculation of bullwhip effect for multi-echelon supply chains under demand and lead time uncertainty. Hence, demand and lead times are calculated via neuro-fuzzy computations at a fuzzy supply chain system, and then the system is simulated via artificial neural networks to measure and evaluate bullwhip effect for various demand and lead time values. Thus, the behaviour of bulwhip effect against demand and lead time variability.
Keywords: Fuzzy supply chains; bullwhip effect; neuro-fuzzy networks; Engineering